Some Results of Principal Fuzzy Metric Spaces and Their Completeness - Wali, Hazim M (Al-Nahrain Journal of Science, 2018)
The main objective of this paper is to introduce the concept of principal fuzzy metric spaces based on the definition of the distance function between fuzzy points. Also, among the obtained results in this paper is the relationship between p-convergent and convergent sequences in principal fuzzy metric spaces, which may be used later to prove the main result of this paper that is the completeness of principal fuzzy metric spaces.